Taxability of Agricultural Income in India: A Study (British Journal of Multidisciplinary and Advanced Studies, 2024)
Tax contributes substantial amount of revenue to the Government. Income Tax Act,1961 exempts agricultural income from taxation. The Act benefits the rural agriculturalists with exiguous income, but large scale farmers and agricultural companies essentially manipulate it and, thus, violate the motive of the clause. While the economists and Government-appointed committees firmly contend for levy of taxes on agricultural income in India on equity and efficacy cogitations, many others withstand cold-bloodedly. There appears monophonic dun to empower the Central Government to levy taxes precisely on agricultural incomes. Apropos the proposed taxation of agricultural income, the present paper examines different aspects of taxation of agricultural income under the Act besides certain primal concerns. Persistent under-taxation of agricultural sector in India precipitates solemn deformity and causes modest overall tax compliance. The researcher, therefore, suggests taxation of agricultural income with others under the Central Government.